A comprehensive overview and qualitative analysis of government-led nutrition policies in Australian institutions - Emalie Rosewarne; Annet C. Hoek; Gary Sacks; Luke Wolfenden; Jason Wu; Jenny Reimers; Kirstan Corben; Michael Moore; Cliona Ni Mhurchu; Jacqui Webster (BMC, 2020)
Abstract Background Institutions are a recommended setting for dietary interventions and nutrition policies as these provide an opportunity to improve health by creating healthy food environments. In Australia, state and territory governments encourage or mandate institutions in their jurisdiction to adopt nutrition policies. However, no work has analysed the policy design across settings and jurisdictions. This study aimed to compare the design and components of government-led institutional nutrition policies between Australian states and territories, determine gaps in existing policies, and assess the potential for developing stronger, more comprehensive policies. Methods Government-led institutional nutrition policies, in schools, workplaces, health facilities and other public settings, were identified by searching health and education department websites for each Australian state and territory government. This was supplemented by data from other relevant stakeholder websites and from the Food Policy Index Australia website. A framework for monitoring and evaluating nutrition policies in publicly-funded institutions was used to extract data and a qualitative analysis of the design and content of institutional nutrition policies was performed. Comparative analyses between the jurisdictions and institution types were conducted, and policies were assessed for comprehensiveness. Results Twenty-seven institutional nutrition policies were identified across eight states and territories in Australia. Most policies in health facilities and public schools were mandatory, though most workplace policies were voluntary. Twenty-four included nutrient criteria, and 22 included guidelines for catering/fundraising/advertising. While most included implementation guides or tools and additional supporting resources, less than half included tools/timelines for monitoring and evaluation. The policy design, components and nutrient criteria varied between jurisdictions and institution types, though all were based on the Australian Dietary Guidelines. Conclusions Nutrition policies in institutions present an opportunity to create healthy eating environments and improve population health in Australia. However, the design of these policies, including lack of key components such as accountability mechanisms, and jurisdictional differences, may be a barrier to implementation and prevent the policies having their intended impact.